Chromium toxicity among leather industry workers in Kolkata-A pilot Study - Maurya, Pawan Kumar; Chakrabarti, Amit; Saha, Asim (International Journal of Occupational Safety and Health, 2023)
Introduction: Chromium (Cr) exposure is known to cause various health issues such as cancer, dermatitis, respiratory problems, etc. The recent exposure of Cr can be determined by analysis of Cr either in blood/urine/plasma, Cr (III) ions cannot permeate through cell membranes of red blood cells (RBC) because their ionic radii are bigger as compared to Cr (VI), and hence Cr in RBC is an indicator for exposure to Cr (VI) ions. The purpose of this study was to investigate chromium exposure, hygienic habits and the occurrence of dermatological problems with leather industry workers in Kolkata. Methods: A total of 68 leather industry workers with minimum work exposure of five years and aged between 18-60 years were recruited for this study. The study protocol included a questionnaire and analysis of Cr in blood and urine samples by GF-AAS. Results: All values were under the Biological Exposure Index (BEI) of 25µg /L at the end of the shift of a five-day work week recommended by the American Conference of Governmental Industrial Hygienists (AcGIH). 15.2% of subjects suffered from dermatological problems at least once in the last year during work in the leather industry. Conclusion: It was found that leather industry workers were not using personal protective equipment and it must be promoted to them for occupational health and safety.